The Brain–Heart Link: A Case Report of a Critically Located Multiple Sclerosis Lesion in the Brainstem Leading to Recurrent Takotsubo Syndrome - Risseeuw, Florentijn; Masrori, Pegah; Baar, Ingrid; Nicolay, Simon; Franssen, Constantijn; Willekens, Barbara (Frontiers in Cardiovascular Medicine, 2021)
Various central nervous system (CNS) diseases, including neurovascular and neuroinflammatory diseases, can lead to stress cardiomyopathy, also known as Takotsubo syndrome (TTS). We present a case of a 69-year-old woman with cardiovascular comorbidities, suffering from repeated episodes of TTS and respiratory failure due to a critical lesion in the brainstem, leading to a diagnosis of multiple sclerosis (MS). Despite aggressive treatment, intractable and recurrent symptoms in our patient occurred. Repeated bouts of autonomic dysfunction and respiratory failure ultimately led to installment of palliative care and the patient passing away. TTS should raise suspicion for underlying neurologic diseases. Thorough questioning of previous neurological symptoms and extensive neurological work-up is warranted. MS should be considered as a trigger of TTS, also in an elderly patient with cardiovascular risk factors.